2005
DOI: 10.1016/j.cellbi.2005.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Two different stages of epidermal growth factor (EGF) receptor endocytosis are sensitive to free ubiquitin depletion produced by proteasome inhibitor MG132

Abstract: Numerous studies implicate proteasomes in the regulation of EGF receptor (EGFR) endocytosis on the basis of the ability of inhibitors to decrease EGFR degradation, but the exact mechanisms remain obscure. We demonstrated that EGFR itself is not a direct target for proteasome, since it is delivered to lysosomes intact. Evidence is presented that the inhibitory effect of MG132 on EGF degradation is due mostly to free ubiquitin depletion resultant from the suppression of proteasomal functioning by MG132. By subce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 44 publications
6
56
0
1
Order By: Relevance
“…The accumulation of unmodified TRC35 (Fig. 3A, lanes 9 and 10 vs. lanes 11 and 12) is probably due to depletion of free Ub in the cell (28). Collectively, these data support the idea that the TRC35 molecules unable to associate with Bag6 at the NLS domain become targets for Ub-dependent degradation through a client-chaperone interaction with Bag6.…”
Section: Get5supporting
confidence: 75%
“…The accumulation of unmodified TRC35 (Fig. 3A, lanes 9 and 10 vs. lanes 11 and 12) is probably due to depletion of free Ub in the cell (28). Collectively, these data support the idea that the TRC35 molecules unable to associate with Bag6 at the NLS domain become targets for Ub-dependent degradation through a client-chaperone interaction with Bag6.…”
Section: Get5supporting
confidence: 75%
“…Monensin can block Golgi transport by preventing the acidification of intercellular compartments and the internalization and recycling of receptors [24]. Serving as an inhibitor for the 26S proteasome, MG132 may deplete cells of free Ub [25], leading to reduction in the internalization of surface receptors. Western blot analysis of the lysates using GalT1p 13 antibodies showed that the GTAP-dependent decrease of long GalT1 was abrogated in the presence of both MG132 and monensin (Fig.…”
Section: Gtap Affects the Internalization Of Surface Galt1 In Escsmentioning
confidence: 99%
“…The ouabain-induced reduction of GlyT2 was completely prevented in the presence of leupeptin, a lysosomal protease inhibitor. The partial effect exerted by the proteasome inhibitor MG132 are probably the result of decreased GlyT2 ubiquitination caused by depletion of the intracellular free ubiquitin pool (Patnaik et al, 2000; Melikova et al, 2006). This conclusion is based on our earlier results showing that endocytosis and further sorting of GlyT2 to the recycling or degradation pathways in neurons depends on ubiquitination, and that the ubiquitination status of the transporter is highly sensitive to ubiquitin homeostasis (de Juan-Sanz et al, 2013).…”
Section: Ouabain Effect On the Transport Activity And Expression Of Gmentioning
confidence: 99%